Development and Usability Perceptions of Spectral Crime Analysis Network Game with Augmented Reality for Ultraviolet-Visible Light Spectroscopy - Hussain, Abbas Ali Iftikhar; Kamari, Azlan; Syamsudin, Frendi Ihwan; Harahap, Lenni Khotimah; Saputro, Sulistyo; Wiyarsi, Antuni; Sukkaew, Adulsman (Balai Publikasi Indonesia, 2026)
The Spectral Crime Analysis Network (SCAN) game was developed using the ADDIE model, used a hybrid augmented reality embedded game-based learning approach and aligned with the learning standards of ultraviolet–visible (UV–Vis) spectroscopy. This game is developed as a learning and reinforcement tool in analytical chemistry instrumentation for undergraduate chemistry students. Based on a survey study conducted on 265 respondents, it was found that the SCAN game demonstrated high usability with mean scores of 3.49 (SD = 0.489) for usefulness, 3.49 (SD = 0.474) for ease of use, 3.48 (SD = 0.504) for ease of learning and 3.53 (SD = 0.476) for satisfaction. Overall, SCAN supports cooperative, technology-enhanced game-based learning, fostering greater interactivity and engagement in chemistry education. This innovation is aligned with the United Nations' Sustainable Development Goal number 4 (SDG4), which is quality education that utilises technology and interactive 21st-century learning.